Mammalian thioredoxin is a direct inhibitor of apoptosis signal-regulating kinase (ASK) 1. - Saitoh, M (1998)
Apoptosis signal-regulating kinase (ASK) 1 was recently identified as a mitogen-activated protein (MAP) kinase kinase kinase which activates the c-Jun N-terminal kinase (JNK) and p38 MAP kinase pathways and is required for tumor necrosis factor (TNF)-alpha-induced apoptosis; however, the mechanism regulating ASK1 activity is unknown. Through genetic screening for ASK1-binding proteins, thioredoxin (Trx), a reduction/oxidation (redox)-regulatory protein thought to have anti-apoptotic effects, was identified as an interacting partner of ASK1. Trx associated with the N-terminal portion of ASK1 in vitro and in vivo. Expression of Trx inhibited ASK1 kinase activity and the subsequent ASK1-dependent apoptosis. Treatment of cells with N-acetyl-L-cysteine also inhibited serum withdrawal-, TNF-alpha- and hydrogen peroxide-induced activation of ASK1 as well as apoptosis. The interaction between Trx and ASK1 was found to be highly dependent on the redox status of Trx. Moreover, inhibition of Trx resulted in activation of endogenous ASK1 activity, suggesting that Trx is a physiological inhibitor of ASK1. The evidence that Trx is a negative regulator of ASK1 suggests possible mechanisms for redox regulation of the apoptosis signal transduction pathway as well as the effects of antioxidants against cytokine- and stress-induced apoptosis.